Application of the method of stationary phase to weakly nonlinear hyperbolic systems asymptotic solving - Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2004)
Method of averaging of first order hyperbolic system with small parameter is presented. The mathematic investigate of this method is based on the method of stationary phase.
Keywords: hyperbolic systems; asymptotics; averaging; small parameter; weakly nonlinear